PERMAINAN EDUKASI PENGENALAN BAHASA PEMROGRAMAN BERBASIS RPG MENGGUNAKAN PENERAPAN ALGORITMA A-STAR: Berbasis Android - Fathurridho, Alief; Fauzy, Rahmat (LPPM Universitas Putera Batam, 2020)
Gaming addiction phenomenon has been happened over the years and keeps increasing over time. This condition very concerning with fact that addicted to the game makes people tend to adopt sloth habit and aside from their obligations activities such study or duties responsibilities, especially on current stay at home policy by the government caused by an ongoing global pandemic. Game junkies who start showing obsessional behavior by mobile or desktop gaming platform are not supposed to be addicted by the game that offers only entertainment purpose, rather try to play the game with the beneficial theme like educational game (Edu-game) that able to deliver knowledge and learning insight. Another common problem people found is the difficulties of learning computer programming. The challenge like monotonous learning media nor dull method to learn has many reported as the main obstacle that prevents learner acquire programming skills in optimal time, even made them lose interest (concede). RPG (Role Play Game) is one of several category gaming themes available that reported success as pedagogic across the field. Equipped with RPG Maker MV, an android based Edu-game is developed and tested, result found Edu-game succeed in deliver computer programming course with 82,4% success rate. Participant tendencies at absorbing the Edu-game divided into three aspects, 58,8% education knowledge absorption, 18,0% enjoying the game aspect, and plot interest also at 18,0% rate